Punishment in contemporary China: its evolution, development and change - Li, Enshen (Routledge studies in crime and justice in Asia and the global South, 2019)
Introduction and theoretical framework -- Punishment and economic liberalization : neoliberal penality, managerial justice and the underclass -- Punishment and populist justice : penal populism with Chinese characteristics -- The emergence of lenient justice : new penal policy in post-reform China -- Community justice in urban China : civic participation, rehabilitative ethos and social stability -- Community corrections in China : restorativeness v managerialism -- Discussion and conclusion